Keanekaragaman Dan Potensi Tumbuhan Pangan Budidaya Di Desa Wisata Cibuntu Kecamatan Pasawahan Kabupaten Kuningan - Wulan Suci Handani (Universitas Tidar, 2021)
Local food that is owned by each region is a great potential for creating food independence and can reduce the dependence of the community on food from outside. Efforts that can be made to meet food needs are to explore every potential local food resource in the area. Cibuntu Village, Pasawahan district, Kuningan regency is one of the village in which the diversity of plant species is stored, especially food plant and has the potential to be developed into tourism. This study aims to examine the diversity of food plant species and the potential for the use of food plants by the community, as well as to determine the distribution of food plants found in the tourist route. This study uses an exploratory method to collect data on the diversity of food plants and interview methods to collect data on the use of food plants community. The result of this study showed that there were 58 species found and include in 33 families. Meanwhile, 52 species of plants use for food were identified that have been used by the community as a source of carbohydrates, protein, vitamins, spices, and drinks. The distribution of food plants is widely spread along the tourist route which is mapped into the base map through GIS.